Volatile Oils and Pectins from Citrus aurantifolia (Lime) and Citrus limonia (lemon). - G. Haggag, Eman; Wahab, S.M. Abdel; El-Zalabany, S.M.; Abou Moustafa, E.A.; El-Kherasy, E.M.; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
Volatile oils were prepared by steam distillation from leaves andpeels of both Citus aurantifolia (lime) and Citrus limonia (lemon).and also by cold pressing both of their fruit peels. The percentageyield of oil for stearn distilled lime peel and leaf were considerably lower than for lemon peel and leaf and lower yet for the cold pressed peel material from both plants. Nineteen components were identified in the oils by TLC and GC. Yields of pectin from the pulp of lime and lemon fruits were about 50% higher using a 0.3% ammonium oxalate solution for extraction rather than a water extraction. Both pectins afforded galacturonic acid. glucose. arabinose and xylose on acid hydrolysis, but the pectin from lime fruit pulp contained more galacturonic acid than the pectin from the lemon fruit pulp, and thus is of higher quality.